Molecular phylogenetics and morphological diversity in Cipura (Iridoideae, Iridaceae): species delimitation and taxonomic revision of the genus, with the description of two new species - Chauveau, Olivier; Báez-Lizarazo, Mabel R.; Aguiar, Antonio J.c.; Stiehl-Alves, Eudes M.; Souza-Chies, Tatiana T.; Eggers, Lilian (Phytotaxa, 2025)
Two new species of Cipura are described from the Cerrado Biome (Brazil): Cipura kalunga, from the northern mesoregion of Goiás state, and C. mestrensis, previously confused with C. formosa, and found in the states of Bahia, Goiás, and Tocantins. A comprehensive review of herbarium specimens combined with fieldwork enabled molecular and morphological analyses to elucidate the phylogenetic relationships within Cipura and assess the taxonomic status of the two new species. The new taxonomic entities are described, illustrated, compared with morphologically related species and an amended description of C. formosa is proposed. Distribution maps and phenological data are also provided. Taxonomical and nomenclatural notes, typifications, conservation assessments and an identification key for the different species of Cipura are included. Phylogenetic analyses revealed two major lineages, distinguished by the morphology of the inner tepals, and 12 distinct taxa are recognized within the genus, of which three are only known from morphology.